News on pediatric urology - Giuseppe Masnata; Valeria Manca; Laura Chia; Francesca Esu (Hygeia Press di Corridori Marinella, 2015)
Pediatric urology is a pediatric speciality dedicated to the diagnosis and treatment of congenital and acquired genitourinary tract diseases. It is a speciality that is rapidly changing, thanks to the technological development that has been emerging in recent years. There have been important diagnostic and therapeutic news. Congenital anomalies of the kidneys and urinary tract (CAKUT) include various entities of structural malformations that result from defects in their morphogenesis. Clinical research and genetic studies on the origins of CAKUT are quickly evolving, with significant growth of high-quality research. Management goals of CAKUT include prevention of febrile urinary tract infections (UTIs) in newborns and toddles and renal injury, while minimizing the morbidity of treatment and follow-up. Treatment options include observation with or without continuous antibiotic prophylaxis (CAP) and surgical correction. Now, randomized controlled studies show that children with normal urinary tracts or low-grade vesicoureteral reflux (VUR) do not benefit from prophylaxis. All children with known mechanical or functional obstructions of the urinary tract are considered to have UTI. Functional obstruction often results from lower urinary tract dysfunction (LUTD) of either neurogenic or non-neurogenic origin and dilating VUR. The role of bladder and bowel dysfunction (BBD) in children with UTI and the long-term risk of renal scarring have shed new light on treatment strategies. Often it is BBD, rather than reflux, that causes UTI in children older than 2 years. Pediatric urology has evolved in recent years, with a greater focus on bladder and renal function, minimally invasive treatment, evidence-based interventions, and guideline adherence. Other topics in pediatric urology include urinary incontinence in children with special needs and the use of robot-assisted laparoscopic surgery (RALS) in children, with advantages over conventional laparoscopic surgery.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)